2017
DOI: 10.1212/wnl.0000000000003918
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant and antiplatelet use in seniors with chronic subdural hematoma

Abstract: Anticoagulant medication was associated with increased rebleeding risk in older adults with cSDH. However, antiplatelet medication was not associated with increased risk of rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 30 publications
3
51
0
3
Order By: Relevance
“…Current clinical guidelines on perioperative antithrombotic use emphasize an individual risk assessment with no clear guidance on the optimal timing of recommencing antithrombotic drugs. 5 An international survey of perioperative acetylsalicylic acid use in CSDH patients 6 confirms the significant variation in clinical practice shown in previous systematic reviews 2,8 and in our analysis. One retrospective cohort study compared outcomes in those who restarted on their antithrombotic drugs to those who did not.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Current clinical guidelines on perioperative antithrombotic use emphasize an individual risk assessment with no clear guidance on the optimal timing of recommencing antithrombotic drugs. 5 An international survey of perioperative acetylsalicylic acid use in CSDH patients 6 confirms the significant variation in clinical practice shown in previous systematic reviews 2,8 and in our analysis. One retrospective cohort study compared outcomes in those who restarted on their antithrombotic drugs to those who did not.…”
Section: Discussionsupporting
confidence: 87%
“…These inconsistencies may stem from the differing study design of CSDH studies. 2,7,8,12 In our secondary analysis of this large cohort, we found no discernible difference in recurrence risk among those on previous antithrombotic drugs. A longer washout period of antiplatelet before an operation did not provide observable benefits.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Antiplatelet drugs did not increase the CSDH recurrence rate following BHD. Similarly, a recent systematic study showed that anticoagulant drugs increased re-bleeding on the operation side of CSDH, but antiplatelet therapy did not [40]. However, this result is controversial as in other studies, antiplatelets or anticoagulants were not associated with CSDH recurrence [16,36,41].…”
Section: Discussionmentioning
confidence: 92%